A Comparative Study between Intravaginal Sponges and Prostaglandin Injection and their effect on reproductive performance in Awassi sheep (Journal of Hama University, 2020)
The objective of this study was to compare between two methods of estrus synchronization (progesterone-impregnated intravaginal sponges and intramuscular (IM) injection of prostaglandin hormone) within the reproductive season and their effect on some reproductive parameters in Awassi ewes. Thirty ewes were equally divided into two groups (G1 and G2). Intravaginal sponges impregnated with 60 mg of Medroxy Acetate Progesterone (MAP) were inserted into the ewes of the first group for 14 d, and were injected at the time of the withdrawal of sponges with 500 IU of equine Chorionic Gonadotrophin (eCG) at the first group ewes (G1). The animals in second group (G2) were injected with double dose of 125μg of prostaglandin (PGF2α) intramuscularly (IM) at 9 days apart. The ewes were naturally mated with fertile rams (ram / 5 ewes). The results showed that there were no significant differences between groups (G1 and G2) in the estrus response (100% and 86.67%, respectively), while there were significant differences in the average time to onset of estrus (38.8 ± 4.45 h and 53.07 ± 4.13 h) and the average duration of estrus (33.20 ± 3.09 h and 28.61 ± 3.59 h, respectively). Also, the pregnancy rate was significant difference (P